2002
DOI: 10.1093/brain/awf142
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a newly identified serine protease in CNS demyelination

Abstract: We have identified a novel serine protease, myelencephalon-specific protease (MSP), which is preferentially expressed in the adult CNS, and therein, is abundant in both neurones and oligodendroglia. To determine the potential activity of MSP in CNS demyelination, we examined its expression in multiple sclerosis lesions and in two animal models of multiple sclerosis: Theiler's murine encephalomyelitis virus (TMEV) and myelin oligodendrocyte glycoprotein (MOG)-induced experimental allergic encephalomyelitis (EAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
186
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(199 citation statements)
references
References 64 publications
12
186
0
1
Order By: Relevance
“…Thus, with regard to enzymatic activity toward myelin-related and extracellular proteins and autolytic properties, hK6 and rat MSP appear to be true functional homologues. The ability of both rat MSP and hK6 to degrade myelin-associated proteins, coupled with data showing that this enzyme is abundantly expressed within inflammatory cells at sites of demyelination in murine models of multiple sclerosis and associated lesions, supports the idea that this enzyme may play a pivotal role in demyelinating disease (18,26,27,50). Autolytic Activity of hK6 -Determination of the x-ray structure of hK6 provides an opportunity to further characterize the autolytic regulation of MSP/hK6.…”
Section: Human Kallikrein 6 Is Functionally Related To Rat Msp-mentioning
confidence: 75%
See 1 more Smart Citation
“…Thus, with regard to enzymatic activity toward myelin-related and extracellular proteins and autolytic properties, hK6 and rat MSP appear to be true functional homologues. The ability of both rat MSP and hK6 to degrade myelin-associated proteins, coupled with data showing that this enzyme is abundantly expressed within inflammatory cells at sites of demyelination in murine models of multiple sclerosis and associated lesions, supports the idea that this enzyme may play a pivotal role in demyelinating disease (18,26,27,50). Autolytic Activity of hK6 -Determination of the x-ray structure of hK6 provides an opportunity to further characterize the autolytic regulation of MSP/hK6.…”
Section: Human Kallikrein 6 Is Functionally Related To Rat Msp-mentioning
confidence: 75%
“…The biochemical and structural data also support the original hypothesis by Isackson and co-workers (18) that the MSP/KLK6 gene codes for a trypsin-like degradative protease that is expressed in the brain. Since our recent studies implicate excess MSP/hK6 activity in the development of immune mediated demyelination in both animal models of multiple sclerosis and in human multiple sclerosis lesions (27,50), the availability of an atomic model of mature hK6, reported herein, may prove useful in the design of specific and potentially therapeutic inhibitors of this unique enzyme.…”
Section: Human Kallikrein 6 Is Functionally Related To Rat Msp-mentioning
confidence: 93%
“…It has been suggested that oligodendrocytes and myelin have endogenous protease activity with the potential to degrade myelin proteins (Sato et al, 1982;Berlet et al, 1984;Chantry et al, 1989;Scarisbrick et al, 2002;Terayama et al, 2005b). The in vitro biochemical assay showed that neuropsin is capable of degrading MBP (He et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study has demonstrated that traumatic injury to the spinal cord causes changes in the expression of protease M/neurosin in oligodendrocytes and their progenitors [20]. Scarisbrick et al [5,16,17] Then adjusted pH to 7.3 with 1 M Tris-HCl, pH 7.5.…”
Section: Introductionmentioning
confidence: 99%